Development of an in vitro model for studying the penetration of chemicals through compromised skin. Issue 1 (February 2015) - Davies, Diane J.; Heylings, Jon R.; McCarthy, Timothy J.; Correa, Catherine M.
Highlights Tape stripping has been evaluated to develop an in vitro model of compromised skin. Electrical Resistance, Trans-Epidermal Water Loss and Tritiated Water Flux were used. Skin stripping regimes were used to remove different proportions of the stratum corneum. Electrical Resistance proved to be a rapid and robust model for compromised skin.